Students’ mathematics performance and their attitude toward the learning of mathematics: an attempt to explore their relationship - Barkatsas, Anastasios; Gialamas, Vasilis; Karageorgos, Dimitris; Kasimatis, Katerina (NOMAD Nordic Studies in Mathematics Education, 1998)
The present study was an exploratory study aimed at investigating the relationship between Year 7 students’ attitudes towards mathematics and their mathematics performance. Using random sampling 29 High Schools were selected from all over the country. The final sample comprised 714 Year 7 students. The research revealed that high performance in mathematics is associated with more positive students’ attitudes toward mathematics learning. The most significant finding of the study is that Year 7 students in Greek High schools demonstrated a serious weakness in solving real life problems using the mathematics they have been taught.